One-Time Cortical Lamina: A New Technique for Horizontal Ridge Augmentation. A Case Series - Foti, Vincenzo; Savio, Davide; Rossi, Roberto (British Journal of Healthcare and Medical Research, 2021)
The aim of this case series is to introduce the One-Time Cortical Lamina Technique, a simplification of the F.I.R.S.T. (Fibrinogen-Induced Regeneration Sealing Technique) in cases where only horizontal augmentation is needed. The indications for this technique are ASA2 and ASA1 anxious patients. Pre-requisites for this surgical technique are: a good amount of keratinized tissue, sufficient alveolar ridge width for placement of implants, thickness of vestibular bone at CBCT planning less than 1 mm with risk of threads exposure. Five patients with horizontal deficiencies were selected to test the efficacy of this approach. The defects were augmented using a porcine cortical bone lamina in combination with collagenated porcine bone mixed with fibrin sealant. The cortical lamina was placed only buccal to the implants and stabilized with fibrin sealant, without pins or screws. Upon completion of the implant surgery, healing abutments were connected to the implants and the soft tissue sutured around them. The healing was uneventful in all cases. Six months after surgery impressions for final restorations were taken and screwed crowns delivered. The new volume had hard consistency and the follow-up CBCT measured an average of 4.17 mm of horizontal bone augmentation. One to three years of follow up demonstrated the maintenance of vestibular volume, hard consistency and clinical stability. Intraoral X-rays showed no marginal bone loss. An advantage of this technique could be the one stage surgery that creates a stable environment for regeneration from day one.